Psychiatric adverse reactions to non-selective RET multi-kinase inhibitors: a large-scale pharmacovigilance analysis - Wang, Xuyan; Yin, Donghong; Tang, Yang; Xiao, Feng; Wang, Shuyun (Frontiers in Pharmacology, 2023)
Objective: The development of non-selective multi-kinase inhibitors (MKIs) has improved the survival outcomes of patients with cancers. Psychiatric disorders represent an MKIs related AE of particular concern, as they are often ignored and may harm the patient's personal and social functioning. Therefore, we use the public database to describe and evaluate psychiatric adverse events related to various non-selective RET MKIs. Provide evidence for optimizing drug administration in the clinic. Methods: We analyzed spontaneous reports submitted to the Food and Drug Administration Adverse Events Reporting System (FAERS) in an observational and retrospective manner. Selecting psychiatric AEs to non-selective RET multikinase inhibitors (sorafenib, lenvatinib, vandetanib, cabozantinib, and sunitinib). We used Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) algorithms to analyze suspected adverse reactions of psychiatric related induced by non-selective RET MKIs between